2014
DOI: 10.17556/jef.95780
|View full text |Cite
|
Sign up to set email alerts
|

Okul Öncesi Dönem Çocuklarının Mizaç Özellikleri İle Dil Becerileri Arasındaki İlişkinin İncelenmesi

Abstract: The investigation of relationship between children temperament and language skills in preschool children

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
2
0
3
Order By: Relevance
“…Linguistic development has important effects on the development of the child in other areas (cognitive, affective and social). In this respect, determination of the factors affecting linguistic development is of vital importance in terms of determining the responsibilities to be fulfilled by families, teachers and other adults [66]. Given that linguistic development has significant influence on the cognitive, affective and social development of children, it seems to be necessary to determine the factors affecting this development and to elicit their predictive effects.…”
Section: Introductionmentioning
confidence: 99%
“…Linguistic development has important effects on the development of the child in other areas (cognitive, affective and social). In this respect, determination of the factors affecting linguistic development is of vital importance in terms of determining the responsibilities to be fulfilled by families, teachers and other adults [66]. Given that linguistic development has significant influence on the cognitive, affective and social development of children, it seems to be necessary to determine the factors affecting this development and to elicit their predictive effects.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the research on the temperament characteristics of children in the literature indicate that the temperament characteristics affect the emotions, behavior, skills, adaptation and learning of the child in other areas (Coplan, Wichman and Lagace-Seguin, 2001;Yoleri and Küçükyeşil, 2014;Zembat, Koçyiğit, Yavuz and Tunçeli, 2018). In this study, it was revealed that self-regulation skill was the predictor of play interaction and negative temperament traits (regression) were predictive of play disruption behavior.…”
Section: Discussionmentioning
confidence: 50%
“…Alan yazında çocukların mizaç özellikleri ile ilgili araştırma sonuçları mizaç özelliklerinin çocuğun diğer alanlardaki duygu, davranış, beceri, uyum ve öğrenmelerini etkilediğine (Coplan, Wichman ve Lagace-Seguin, 2001;Yoleri ve Küçükyeşil, 2014;Zembat, Koçyiğit, Yavuz ve Tunçeli, 2018) işaret etmektedir. Bu araştırmada öz-düzenleme becerisinin oyun etkileşiminin, olumsuz mizaç özelliklerinin (tepkisellik) ise oyun bozma davranışının yordayıcısı olduğu ortaya çıkmıştır.…”
Section: Tablo 5 Mizaç Ve öZ-düzenlemenin Oyun Davranışı-oyundan Kopma Alt Boyutunu Yordayıcı Rolüne Ilişkin Regresyon Analizi Sonuçlarıunclassified
“…Araştırmada ortaya çıkan bu sonuç, alanyazında da vurgulandığı gibi, iletişimin iki yönlü bir süreç olduğunu ve olumlu iletişim özelliklerinin kaynak ve hedef arasındaki olumlu iletişim sürecini pekiştirdiğini destekler niteliktedir. Alanyazında yapılan araştırmaların sonucunda (Arı & Yaban, 2016;Aytemiz, 2010;Barber, 2001;Dereli & Dereli, 2017;Dixon & Shore, 1997;Gözün-Kahraman & Gökşen, 2021;Ladd & Burges, 1999;Morales vd., 2000;Slomkowski vd., 1992;Spere vd., 2004;Yağmurlu & Altan, 2010;Yağmurlu, Sanson & Köymen, 2005;Yaman, 2018;Yoleri & Küçükyeşil, 2014), çocukla iletişimdeki olumlu ve demokratik ebeveyn tutumlarının çocuklardaki sıcakkanlılık mizaç özelliğini, duygu düzenleme becerilerini, olumlu sosyal davranışları ve bilişsel becerileri öğrenmeyi anlamlı derecede yordadığı bulgusuna ulaşılmıştır. Ebeveyn davranışlarının oluşmasında, ebeveynlerin kişisel özellikleriyle birlikte, çevresel unsurlar ve çocuğun mizacı gibi kişisel özellikleri de etkilidir.…”
Section: Sonuç Tartışma Ve öNerilerunclassified